Interpreting apocalyptic literature : an exegetical handbook - Taylor, Richard A (Grand Rapids, MI, Kregel Academic, 2016)
Taylor begins with a helpful introduction to the genre of apocalyptic literature; surveys its purpose, message, and primary themes in the Old Testament; and then discusses critical questions and key works for further study. He also provides guidelines for interpreting apocalyptic texts. Included are sample sermon texts from apocalyptic literature. Using texts from both Daniel and Joel, Taylor shows how to outline apocalyptic passages. - from back of book
Includes bibliographical references
Keywords: Bible. -- Criticism, interpretation, etc; Apocalyptic literature -- History and criticism